Alteration in TSH levels during Ramadan in non fasting levothyroxine treated patients living with fasting family members - Aytekin, Alper; Köroğlu, İpek; Sayiner, Zeynel Abidin; Karaçalı, Mehmet; Baloğlu Akyol, Elif Melis; Akarsu, Ersin (The European Research Journal, 2025)
Objectives: During Ramadan, lifestyle changes may affect thyroid function not only in fasting individuals but also in those who do not fast. This study examined the impact of Ramadan-related behavioral shifts on thyroid-stimulating hormone (TSH) levels in patients receiving stable levothyroxine therapy. Methods: This observational before-and-after study, conducted between January 2023 and January 2024, included 116 hypothyroid patients on stable levothyroxine (LT4) therapy. Serum TSH, free thyroxine (fT4), and free triiodothyronine (fT3) levels were measured one month before and within one week after Ramadan. Patients were categorized as fasting or non-fasting, and completed a structured questionnaire regarding medication timing, fasting behavior, and lifestyle changes. Linear regression analysis was used to identify predictors of post-Ramadan TSH changes. Results: TSH levels significantly increased after Ramadan in the overall cohort (mean±SD: 3.03±3.24 vs. 4.77±7.83 mU/L; P=0.028), while fT3 and fT4 levels remained unchanged (P=0.14 and P=0.72, respectively). Among fasting patients (n=72), TSH rose from 3.26±3.26 to 4.80±8.58 mU/L (P=0.47), whereas non-fasting patients (n=44) showed a significant increase from 2.65±3.21 to 4.73±6.51 mU/L (P=0.006). Polypharmacy was associated with increased odds of post-Ramadan TSH elevation (OR=2.67, 95% CI: 1.25–5.73, P=0.01). Among non-fasting patients, those who reported changes in sleep or meal patterns during Ramadan (n=28) experienced a significantly higher increase in TSH compared to those without such changes (ΔTSH: 2.47±3.88 vs. 0.81±2.12 mU/L, P=0.02). Conclusions: Patients receiving LT4 therapy who do not fast during Ramadan may still exhibit significant TSH variability, likely due to behavioral and circadian disruptions. These findings emphasize the importance of proactive monitoring and targeted education for all hypothyroid patients during Ramadan, irrespective of fasting status.